A Note on Inflation Persistence - Steinar Holden; John C. Driscoll (Norges Bank, 2002)
Macroeconomists have for some time been aware that the New Keynesian Phillips curve, though highly popular in the literature, cannot explain the persistence observed in actual inflation. We argue that one of the more prominent alternative formulations, the Fuhrer and Moore (1995) relative contracting model, is highly problematic. Fuhrer and Moore (1995)'s formulation generates inflation persistence, but this is a consequence of their assuming that workers care about the past real wages of other workers. Making the more reasonable assumption that workers care about the current real wages of other workers, one obtains the standard formulation with no inflation persistence.
hdl:11250/2498659
Keywords: E31; E3; E5; 330; New Keynesian Phillips curve; Fuhrer and Moore model; inflation persistence